Pirates of Silicon Valley [videorecording (DVD)] (Warner Home Video, 1999)
Steve Jobs and Bill Gates have pioneered an industry that literally transformed the entire world. The passion, luck and genius of these quirky visionaries is presented in this portrayal of the fierce and often humorous battle to rule the fledgling personal computer empire.